Ecological Initiatives of the Global Catholic Climate Movement - Dall’Oglio, Cecilia (Studia Ecologiae et Bioethicae, 2020)
This paper presents the structure and main aims of Global Catholic Climate Movement (GCCM): an international organization serving Catholics all over the world to promote ecological values. It points to a close connection between teaching of the Catholic Church and care about the creation. The efforts to prevent effects of climate changes are indicated as an important mission for believers, in accordance with Pope Francis’ encyclical Laudato si’. There are three major dimensions describing how to bring Pope’s teaching to life: spiritual dimension, lifestyle dimension and public policy dimension. In this article one can find many examples of good practices, which have been in the process of being realized since the GCCM was set up in 2015. The main content is followed by the detailed calendar, which shows the crucial achievements of GCCM.